Primary intraocular lymphoma – 2.5 year follow-up - Cholewa, Monika; Chosia, Maria; Jarema, Alina; Lubiński, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Purpose: To present clinical manifestation, diagnosis and treatment of a patient with the primary intraocular lymphoma at 2.5 year follow-up. Patient and methods: Phaco-PPV with silicone oil tamponade was performed in a 62 year old man with a diagnosis of recurrent bilateral uveitis of unknown etiology complicated by cataract. The creamy-yellow infiltrates were identified and aspirates were collected for immunocytochemical evaluation during the surgery – B-cell lymphoma was diagnosed. The results of additional tests – hematologic workup, head and orbit neuro-imaging – were within normal limits. The patient has been treated with regular intraocular injections of Methotrexate at a dose of 400 µg/0.1 ml to both eyes for 2.5 years. Regular routine ophtalmic examinations were performed during the said follow-up period. Results: The lymphocyte infiltrations in both eyes regressed during therapy. The best corrected distance VA remained stable and was 0.2 in RE and 0.3 in LE (Snellen). The intraocular pressures and anterior segments in both eyes were normal. The new small lymphocyte infiltrates were observed in the fundi and were successfully treated with additional Methotrexate injections. Methotrexate treatment was augmented with a single laser endophotocoagulation in the LE and 2, 3-time argon laser photocagulation in both eyes. To date, there no systemic symptoms of the disease have been observed. Conclusions: Local chemotherapy with Methotrexate may be an effective and safe treatment of primary intraocular lymphoma. However, due to high potential for systemic and local spread, patients should be monitored on a regular basis by ophthalmologists and oncologists.